(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
Clinical and laboratory symptoms of blastocystosis in patients with HIV infection were studied in this article. The study was conducted on 30 patients treated in the Samarkand Regional Infectious Diseases Hospital in 2021-2023 . General clinical, parasitological, biochemical, serological, molecular-genetic, instrumental methods were used in the research work. From the gastrointestinal tract in patients: nausea, loose stools or constipation, pain in the epigastric area, around the navel and in the left flank area were found more in the main group than in the control group. One of the clinical manifestations of blastocystosis is allergic symptoms. In the studied patients, urticaria was observed in 1 (7.14%) patient, dermatosis in 2 (14.2%) patients, skin itching in 4 (28.5%) patients, and allergic rhinitis in 1 (7.14%) patient.